2021
DOI: 10.1186/s11689-021-09381-2
|View full text |Cite
|
Sign up to set email alerts
|

Visual and somatosensory feedback mechanisms of precision manual motor control in autism spectrum disorder

Abstract: Background Individuals with autism spectrum disorder (ASD) show deficits processing sensory feedback to reactively adjust ongoing motor behaviors. Atypical reliance on visual and somatosensory feedback each have been reported during motor behaviors in ASD suggesting that impairments are not specific to one sensory domain but may instead reflect a deficit in multisensory processing, resulting in reliance on unimodal feedback. The present study tested this hypothesis by examining motor behavior a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 91 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…As is well known, accumulated evidence has shown that deficits in sensorimotor integration and control in ASD are closely related to self-care performance in social life. 108 , 109 Our results of GMV aberrance in the cerebellum anterior and posterior lobes may be related to abnormal sensorimotor function and cognitive function, respectively. Therefore, the topography of sensorimotor and cognitive subregions of the cerebellum emerge because the cerebellum form s closed-loop circuits with sensorimotor and cognitive areas of the cerebral cortex.…”
Section: Discussionmentioning
confidence: 71%
“…As is well known, accumulated evidence has shown that deficits in sensorimotor integration and control in ASD are closely related to self-care performance in social life. 108 , 109 Our results of GMV aberrance in the cerebellum anterior and posterior lobes may be related to abnormal sensorimotor function and cognitive function, respectively. Therefore, the topography of sensorimotor and cognitive subregions of the cerebellum emerge because the cerebellum form s closed-loop circuits with sensorimotor and cognitive areas of the cerebral cortex.…”
Section: Discussionmentioning
confidence: 71%
“…As the first sensory system to fully develop (Piontelli, 2015), touch is vital during early childhood development (Blackwell, 2000; Cascio et al, 2019; Rheingold, 1966) and provides feedback on the relationship between the self and the physical world (Riemann & Lephart, 2002). While research on somatosensation in autism has increased in recent years (Buyuktaskin et al, 2021; Noda et al, 2022; Shafer et al, 2021), the great majority of studies have focused on auditory and visual perception, despite evidence suggesting that over sixty percent of people with autism have higher tactile sensitivity than their neurotypical (NT) peers (Tomchek & Dunn, 2007). These alterations in sensory processing can affect quality of life and may have downstream effects on higher-order features such as social communication and repetitive behaviors that are characteristic in autism (Kawakami & Otsuka, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In a reach-to-grasp paradigm, Mari and collaborators (2003) observed a lack of coordination between the reaching and the grasping phases in ASD, especially in those with lower intelligence quotient (IQ). Yet, recent studies challenged this view reporting a disrupted feedforward and feedback control in ASD individuals (Mosconi et al, 2015; Shafer et al, 2021; Wang et al, 2015; see also Ming et al, 2007; Sacrey et al, 2014 for review). Previous studies reported that adding a visual distractor to a task influenced both feedforward and feedback control of typical children, but not of children with ASD (Dowd et al, 2011), highlighting their preference for proprioceptive over visual feedback (Lidstone & Mostofsky, 2021; see also Glazebrook et al, 2009 for visuo-proprioceptive integration).…”
Section: Introductionmentioning
confidence: 99%